Material Sources of Algerian Family Law - Article 8 as an Example- Les sources matérielles du droit de la famille algérien - Exemple de l’article 8- - djafferi, Karim; boudjemaa, Hammad (Journal of Social Sciences and Humanities, 2024)
The phenomenon of polygamy is one of the most important issues in personal status, addressed by Algerian legislation in family law, where its provisions are found in Article 8 of the Family Law, as amended by Order 05/02. Due to the importance of the phenomenon and the debate it raises, it was necessary to research the material sources upon which the Algerian legislator relied in formulating Article 8. Considering Algerian custom, it is evident that there is a difference in societal views on the matter from one region to another. For example, in the southern regions of Algeria, polygamy is considered normal, whereas in the northern regions and major cities, it is seen as abnormal and deviating from the norm. This indicates that the Algerian legislator was wise in Article 8 of the Family Law, taking into account Algerian custom that accepts polygamy by allowing it, while also considering the custom that does not accept polygamy by placing restrictive conditions. Thus, it is realized that custom is one of the sources of Article 8 of Algerian family law. Examining Arab laws that range from prohibition to permission of polygamy, and since these laws preceded Algerian family law, it is not excluded that they are one of the sources relied upon by the Algerian legislator in formulating Article 8. As for Islamic law, it addressed the issue of polygamy in a way that ensures the rights of all, yet the Algerian legislator did not solely rely on it as a source but only took a part of it. It is one of the sources relied upon by the Algerian legislator. Therefore, the Algerian legislator relied on multiple sources in formulating Article 8 of the Family Law, including Sharia, custom, Islamic law, and Arab laws.